THE ADAPTION OF WOMEN WHO WORK AS A SPLIT STONE IN CIAPUS RIVER, BOGOR - Nurul Qomariyah; MM. Nilam Widyarini (Jurnal Psikologi, 2006)
There are many evidences to show that there’s been a perspective movement about attitude, activity,gender role differences between men and women that affect another movement in the work field for bothmen and women. Women can be found work as a driver, labor, sailor, lawyer and many more. On theother side, men are also can be found work as designer, stylist, capster, dancer, and many more. Thedemand inside herself make women who work in masculine work field feels uncomfortable because it’snot something that usual for her stereotype work field. The aim of this study is to know the descriptionabout the adaptation, its processes, and factors influencing the women’s adaptation who work inmasculine work field with qualitative method. Participant of this study is a women who work as splitstone in Ciapus river, Bogor. The result shows participant has a good adaptation that can be seen in heradaptation aspects and characteristics.Key words: adaptation, working women, masculine work field